1985
DOI: 10.1002/j.1875-9114.1985.tb03407.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Neomycin Sulfate and Erythromycin Base Before Colon Surgery: A Comparison of Serum and Tissue Concentrations

Abstract: It is accepted that the use of oral neomycin sulfate and erythromycin base before colon surgery results in decreased numbers of intestinal bacteria. Intraluminal levels of these agents are reported to be very high, but systemic availability is still debated. The systemic levels were studied in 8 patients undergoing colon surgery. Each patient received neomycin sulfate and erythromycin base, 1 g each, 19, 18 and 9 hours preoperatively. Twelve samples from serum, one from wound muscle and one from the intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The combination of oral neomycin and erythromycin has been recommended for use as preoperative antibiotic prophylaxis for colorectal surgery in an advisory statement from the Medicare National Surgical Infection Prevention Project35. Outside North America, this figure is much lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of oral neomycin and erythromycin has been recommended for use as preoperative antibiotic prophylaxis for colorectal surgery in an advisory statement from the Medicare National Surgical Infection Prevention Project35. Outside North America, this figure is much lower.…”
Section: Discussionmentioning
confidence: 99%
“…There was no association between the combination of antibiotics and outcome, as long as an aminoglycoside was included. Aminoglycosides administered orally reach very low levels in the circulation35, and toxicity is vanishingly rare. It is suggested that future ERAS protocols should factor in a combination of MBP and short‐course oral antibiotic prophylaxis with an aminoglycoside and metronidazole, and i.v.…”
Section: Discussionmentioning
confidence: 99%
“…2 Pharmacokinetic studies showed that kanamycin (or neomycin) was not absorbed and remained bacteriologically active within the lumen of the colon, while high intraluminal and serum levels of metronidazole (or erythromycin base) were found at the time of surgery (8 a.m.). 17 We evaluated a brief-course preoperative colon preparation with a 3-day postoperative prophylaxis of systemic antibiotics. The issue was whether or not the concominant administration of preoperative oral antibiotics with perioperative parenteral antibiotics was more effective in decreasing postoperative infection than a parenteral regimen alone.…”
Section: Discussionmentioning
confidence: 99%
“…Bacitracin has been used orally for the treatment of Clostridium difficile-associated diarrhoea and colitis (3,4). Oral neomycin is indicated for suppression of intestinal bacterial flora in patients undergoing colorectal surgery (5,6) and as a means of decreasing colonic bacteria and the production of ammonia in hepatic encephalopathy (7). Recently, it has been reported that the oral administration of neomycin plus bacitracin prevents diarrhoea induced by chemotherapy drugs used in the treatment of advanced colorectal cancer (8).…”
Section: Introductionmentioning
confidence: 99%